The Problem With Eric Voegelin's Historical Conception of Philosophy - Bourne, Alexander David (My University, 1981)
This thesis is a critical examination of Eric Voegelin's historical conception of philosophy. Voegelin is of particular relevance to a student of religion in that he argues that philosophy and history can only be properly understood in terms of a "divine ground." Central to this thesis, then, is the attempt to understand in what sense philosophy and history can be spoken of in relation to a divine ground, how that ground is known, and what it is.
Voegelin's arguement is wide-randging: it involves 1) a powerful criticism of contemporary understandings of science and philosophy; 2) a detailed argument about the proper nature of political science; 3) an extensive analysis of the main political-philosophical writings of the West, particularly those of Plato and Aristotle. The scope of his writings and so of his argument presents a problem for any analysis - but I will be selective in terms of the issues raised in the first paragraph.
A substantial part of this thesis involves the attempt to clarify and recount Voegelin's argument as he makes it in his various writings. However, I think that certain critical questions can be raised about. his position and these will be developed as his position is clarified.
Keywords: Religion; Religion